Forgiveness among Javanese Ethnicity Mancanegari Subculture: A Case Study in Indonesia - Nashori, Fuad; Gusniart, Uly; Subandi, M.A; Diana, Raden Rachmy; Saputro, Iswan (International Journal of Psychosocial Rehabilitation, 2020)
This study was aimed to examine a model of forgiveness among Javanese ethnicity from Mancanegari subculture. The hypothesis was the model of the effect of religiosity on forgiveness with mediating effects through agreeableness trait and interpersonal attachment showed a good fit to the data. This study has used the forgiveness, agreeableness trait, religiosity, and interpersonal attachment scales. Participants were 275 Javanese ethnicity Mancanegari subculture (the area of culture in East Java). The result of this study indicated that the model of the effect of religiosity on forgiveness with the mediating effect of agreeableness trait and interpersonal attachment was fit to the data. It was confirmed that forgiveness influenced by religiosity with agreeableness trait and interpersonal attachment as mediating effects among Mancanegari-Javanese.